Promosi Melalui Endorse Pada Produk Kosmetik Wardah Ditinjau Dari Perspektif Bisnis Syariah (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam UIN Fatmawati Sukarno Bengkulu) - Effrianti, Yeka; Wahyuni, Eka Sri (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2024)
This study aims to determine promotion through endorsement in increasing consumer buying interest in wardah cosmetic products and the application of sharia business principles in the promotion of endorsement on wardah cosmetic products. This study used descriptive qualitative research method. Data collection techniques of interviews, observation and documentation. Data analysis techniques use descriptive analysis with stages of data reduction, data presentation, and conclusion. The result of this study is that promotion through endorsements on wardah cosmetic products is very influential in increasing consumer buying interest if done honestly, transparently, and with good and correct descriptions and ways. Therefore, honesty, transparency in endorsing and also describing products well are needed in promoting products with endorsements. Viewed from the perspective of sharia business, the promotion of endorsement on wardah cosmetic products carried out by Dewi Sandra is able to increase consumer buying interest and has also fulfilled the principles of sharia business in promoting by endorsing wardah cosmetic products.